2019
DOI: 10.1002/jia2.25372
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of pregnant women in antiretroviral drug research: what is needed to move forwards?

Abstract: Introduction To adequately ascertain drug safety and efficacy, drug trials need to include participants from all groups likely to receive the medication following approval. Pregnant women, however, are mostly excluded from trials, and women participating are often required to use highly effective contraception and taken off study product (even off study) if they conceive. There is little commercial incentive for including pregnant women in clinical trials, even when preclinical animal and human pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Therefore, enrolment of adolescent girls also depends on the country policy that dictates the age when adolescent girls can use contraceptives. Especially in resourcelimited settings key issues pertaining to the use of contraceptives in adolescent girls such as cultural norms, religious beliefs, community perspectives and stigma (for HIV and contraceptive use), might pose major enrolment concerns and could be addressed during the trial planning phase [31]. Raising community awareness and education is also crucial [32].…”
Section: Contraception In Adolescencementioning
confidence: 99%
“…Therefore, enrolment of adolescent girls also depends on the country policy that dictates the age when adolescent girls can use contraceptives. Especially in resourcelimited settings key issues pertaining to the use of contraceptives in adolescent girls such as cultural norms, religious beliefs, community perspectives and stigma (for HIV and contraceptive use), might pose major enrolment concerns and could be addressed during the trial planning phase [31]. Raising community awareness and education is also crucial [32].…”
Section: Contraception In Adolescencementioning
confidence: 99%
“…Clearly, there is an ethical and public health imperative to include pregnant and breastfeeding women in clinical research (28). This need certainly extends to purposefully establishing the safety and efficacy of new HIV treatment and prevention methods in pregnant individuals with or at risk for HIV (5,29). This can be illustrated by the 2019 finding from the Tsepamo study in Botswana that periconceptual dolutegravir use by women living with HIV may increase neural tube defects (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV research community has led the way in many aspects of pharmacological research in pregnant and breastfeeding women, from trial design, advocating for the earlier and routine inclusion of pregnant or potentially pregnant women in such studies, 12 providing guiding principles for the design and analysis of high quality pharmacokinetic studies 13,14 and providing an ethical framework on which to underpin this. 15 A 2016 systematic review of all pharmacokinetic studies in pregnancy identified 198 studies exploring 121 different medications.…”
Section: Hiv Pharmacology Has Led the Waymentioning
confidence: 99%
“…Only a decade later, when registry data had accumulated and the studies were eventually done in pregnant women, did it become clear that there was a species difference in the observed toxicity; no embryotoxicity was observed among pregnant humans. 12,24 The potential benefits of research participation include later access to the fruits of a particular research endeavour: a safe, tolerable and effective drug. Systematic exclusion from research is unjust partly because it results in systematic exclusion from these benefits.…”
Section: Equity Of Access To Researchmentioning
confidence: 99%
See 1 more Smart Citation